Analisis Alih Fungsi Lahan Usahatani Kakao Menjadi Kelapa Sawit di Kecamatan Tinondo Kabupaten Kolaka Timur - Haerul Sada; Ulyasniati Ulyasniati; I Made Sukratman (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to find out what factors influence farmers to convert cocoa plantation land into oil palm plantations in Tinondo District, East Kolaka Regency. The sample used was 32 farmers. The data analysis used is multiple linear regression analysis. The research results can be concluded that the factors that cause the conversion of cocoa land to oil palm are the area of ​​cocoa land, farming experience, environmental factors and regulatory factors. Partially using the t test, cocoa land area with a significant value of 0.000, farming experience with a significant value of 0.000, environmental factors with a significant value of 0.025 and regulatory factors with a significant value of 0.000 in the positive direction and the calculated t value is greater than the t table shows that these variables has a significant influence and is the cause of farmers converting cocoa land into oil palm.